IMPLEMENTASI PASAL 111 AYAT (1) HURUF C ANGKA 5 PERMEN ATR/KBPN RI NOMOR 16 TAHUN 2021 TERHADAP KEWENANGAN NOTARIS MEMBUAT AKTA KETERANGAN WARIS - Yustisia Setiarini Simarmata,; Winanto Wiryomartani, (The Juris, 2021)
A certificate of inheritance is a document of proof from the heirs about the truth that they are the right people and have the right to inherit from the heir. Certificate of Inheritance is required when heirs wish to transfer rights from the heirs. For registration of transfer of land rights or Ownership Rights to Flat Units, based on the Regulation of the State Minister of Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 concerning Provisions for the Implementation of Government Regulation Number 24 of 1997 concerning Land Registration, for Indonesian citizens of Chinese descent: deed of title statement inherited from a Notary. This is in line with Article 15 UUJN, the authority of a Notary to make a deed. Article 111 paragraph (1) Regulation of the Minister of ATR/BPN Number 16 of 2021 concerning the Third Amendment to the Regulation of the Minister of State for Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 concerning Provisions for the Implementation of Government Regulation Number 24 of 1997 concerning Land Registration states the application for registration of the transfer of rights to land rights. Land or Ownership Right to the Flat Unit is submitted by the heirs or their proxies by attaching one of them in point (c) a letter of proof as an heir, one of which in point (5) can be in the form of a deed of inheritance rights from a Notary domiciled at the heir's residence. at the time of death. The basic difference between the two regulations is the position of a Notary who is authorized to make a Certificate of Inheritance for the deceased. Based on this rule, specifically for the object of land rights or Flat Ownership Units, a Certificate of Inheritance can only be made by a Notary who is domiciled at the place of residence of the heir at the time of death. This research uses normative juridical law studies, namely research that is focused on examining the application of rules or norms in positive law.